Early Increases In Blood Lactate Following Injury. Issue 2 (1st June 2002) - Coats, TJ; Smith, JE; Lockey, D; Russell, M
Abstract : Current pre-hospital trauma triage systems are based mainly on physiological parameters, but in compensated shock injury severity may not be immediately obvious, as the physiological parameters remain normal for some time. Serum lactate, measured in hospital, is known to be a predictor of injury severity and outcome. The technology for easy field lactate measurement has recently become available. We found that capillary lactate is elevated in trauma patients in the early phase of the response to injury. There is a moderate correlation (R2 = 0.44) between early lactate levels and injury severity, in patients who might otherwise be difficult to triage. Our aims were: (a) To determine if lactate levels are elevated in the pre-hospital phase of trauma, and to establish whether there is a correlation between pre-hospital lactate and injury severity. (b) To determine if there is a relationship between pre-hospital lactate and injury severity in patients with normal blood pressure and Glasgow Coma Score of greater than 12 ("difficult to triage" group). Methods: Prospective analysis of pre-hospital capillary lactate levels and Injury Severity Score (ISS) in 23 trauma patients attended by the London Helicopter Emergency Medical Service. Results: Capillary lactate is elevated in trauma patients in the early phase of the response to injury. There is a moderate correlation (R2 = 0.44) between early lactate levels and injury severity, in patients who might otherwise be difficult to triage. Conclusions: Lactate is elevated in the earliest prehospital phase of injury following trauma. The potential contribution of this biochemical para-meter to field triage requires further evaluation.